PENGARUH KINERJA KEUANGAN DAN ISLAMIC GOVERNANCE TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PADA BANK SYARIAH - Ferdyan Wana Saputra; Adityawarman Adityawarman (Diponegoro Journal of Accounting, 2016)
This research aims to analyze the factors that affect the disclosure of social responsibility on Islamic banks in Indonesia. The measurement of social responsibility disclosure for Islamic banks to use the ISR Index issued by AAOIFI (Accounting and Auditing Organization for Islamic Financial Institutions) is the international organization that regulates the Islamic financial institutions that exist throughout the world.Samples are included in the bank's Islamic banks, always doing social responsibility reporting in annual reports as well as assessing the level of disclosure of social responsibility for 2010-2014. Samples were selected using purposive sampling method and obtained 55 samples.The data used is secondary data, such as financial statements, annual reports, and ISR Index. Analysis of the data used is descriptive statistics, the classic assumption test, and regression analysis.The results of this study showed that a measure of bank, age, size of bank's Shariah Board of Trustees and the size of the Board of Commissioners effect significantly against the disclosure of social responsibility on Islamic banks. Meanwhile, return on assets and return on equity has no effect significantly against the disclosure of social responsibility on Islamic banking.